LCP Plane Wave Scattering by a Chiral Elliptic Cylinder Embedded in Infinite Chiral Medium - A.-K. Hamid , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
An analytic solution is presented to the scattering of a left circularly polarized (LCP) plane wave from a chiral elliptic cylinder placed in another infinite chiral medium, using the method of separation of variables. The incident, scattered, as well as the transmitted electromagnetic fields are expressed using appropriate angular and radial Mathieu functions and expansion coefficients. The unknown scattered and transmitted field expansion coefficients are subsequently determined by imposing proper boundary conditions at the surface of the elliptic cylinder. Numerical results are presented graphically as normalized scattering widths for elliptic cylinders of different sizes and chiral materials, to show the effects of these on the scattering widths.